Effect of transportation and pre‐slaughter water shower spray with resting on AMP‐activated protein kinase, glycolysis and meat quality of broilers during summer. (27th August 2015) - Xing, Tong; Xu, Xinglian; Jiang, Nannan; Deng, ShaoLin
Abstract: The aim of this study was to determine the effects of pre‐slaughter transport during summer and subsequent water shower spray on stress, postmortem glycolysis, energy metabolism and adenosine monophosphate‐activated protein kinase (AMPK) in Pectoralis major (PM) muscle of broilers. Results indicated that transport during high ambient temperature induced the release of plasma corticosterone, which significantly affected stress conditions. Moreover, we found a lower energy status in the early postmortem period compared to the control group. AMPK was activated in this situation, following by the rapid glycolysis and accumulation of lactic acid, leading to a high incidence of pale, soft, exudative (PSE)‐like meat. Water shower spray with resting after transport relieved the stress situation, recovered energy homeostasis and lessened the deterioration of meat quality. As a key molecular target for the control of energy status, AMPK has a similar potential in regulating postmortem muscle glycolysis of broilers as in mammals.